Analisis Fungsi Tindak Tutur Direktif dalam Konteks Bayar Sewa - Mailawati Mailawati (Diglosia: Jurnal Kajian Bahasa, Sastra, dan Pengajarannya, 2023)
The payment deadline for renting a cost becomes one thing that being anticipated by most people who rent. Even some words from the cost owner still need to be observed well because illocution meanings are inside. This research aims to describe the function of directive speech acts by the cost owner and the effect of renting payment context. This research method is qualitative descriptive by using the WA screenshot documentation method and interviews with all the cost renters. The results show two types of speech act functions, such as collecting and ordering, either directly or indirectly. The direct speech act functions are conveyed more for undergraduate students than for postgraduate students. The functions utilize 5 positive politeness strategies, 3 negative politeness strategies, 1 off-record politeness strategy, and 1 bald-on politeness strategy. The application of these strategies influences by age, status, and power possessed by the owners and tenants of the boarding house. Although the directive speech acts conveyed have the same positive effect. However, the methods and strategies used differ depending on the social factors of both parties.